The risk of chronic traumatic brain injury in professional boxing: change in exposure variables over the past century. Issue 9 (23rd August 2005) - Clausen, H; McCrory, P; Anderson, V
Abstract : Objectives: To determine if boxing exposure has changed over time and hence if current professional boxers are at the same risk of developing chronic traumatic brain injury (CTBI) as historical controls. Design: Literature review of published studies and analysis of data of active professional boxers. Subjects: Professional boxers in the United Kingdom and Australia. Main outcome measures: Boxing history and participation in sparring and professional bouts. Results: Since the 1930s, the average duration of a professional boxer's career has dropped from 19 years to five years, and the mean number of career bouts has reduced from 336 to 13. This is despite no significant decline in participation rates from 1931 until 2002. Conclusions: The incidence of boxing related CTBI will diminish in the current era of professional boxing because of the reduction in exposure to repetitive head trauma and increasing medical monitoring of boxers, with preparticipation medical and neuroimaging assessments resulting in the detection of early and potentially pre-symptomatic cases of CTBI.